Comparison of Cooling Cost Effectiveness Between Unitary and Central Cooling System - Abd Aziz, Azizuddin (2005)
Air conditioning is a basic need in building spaces to provide indoor comfort. This research describes the evaluation of cooling cost effectiveness between unitary and central chiller cooling system. Operational cost involving initial, energy and maintenance for both systems was analysed throughout the life span period. A case study was carried out where cooling load requirement of all conditioned spaces was determined using cooling load temperature difference 1 cooling load factor method. Currently in-use unitary system data was gathered and an all-water type central cooling system was proposed as an alternative. Main equipment capacity of the central system was designed based on cooling load and appropriate heat equation. The study shows that the central system is the better option for high air conditioning application of more than 60 kW heat gain. Although central system first cost is almost double than that of unitary system, it has the advantage of much higher life span. Cumulative cost analysis for the case study indicates that the investment of central system provides a payback period of eight years. In addition, the central system also contributes towards energy conservation by offering lower total power input of its equipment.